2016
DOI: 10.1371/journal.pone.0148812
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Dependency of Laser Speckle Flowgraphy Measurements of Optic Nerve Vessel Microcirculation

Abstract: PurposeTo investigate the relationship between various characteristics of a normal population and laser speckle flowgraphy (LSFG) measurements of mean blur rate (MBR) in the optic nerve head (ONH).MethodsA total of 189 eyes of 189 normal subjects (93 male, 96 female, mean age 45 ± 14 years old, age range: 20–72) without any history of hypertension, hyperlipidemia or diabetes were enrolled. ONH microcirculation was measured with LSFG and overall MBR (MA), vessel-area MBR (MV), and tissue-area MBR (MT) were deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 38 publications
6
44
1
1
Order By: Relevance
“…The results showed that the male group had higher hemoglobin and hematocrit levels and lower ONH blood flow velocity, and the female group had lower hemoglobin and hematocrit and higher ONH blood flow velocity. The multiple regression study showed that sex-related differences were present when the clinical examination data were not included which is consistent with the results of earlier results 25 , 26 . However, the multiple stepwise regression analyses showed that sex was not an independent factor for the ONH-MBR blood flow when clinical examination data were included in the analyses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the male group had higher hemoglobin and hematocrit levels and lower ONH blood flow velocity, and the female group had lower hemoglobin and hematocrit and higher ONH blood flow velocity. The multiple regression study showed that sex-related differences were present when the clinical examination data were not included which is consistent with the results of earlier results 25 , 26 . However, the multiple stepwise regression analyses showed that sex was not an independent factor for the ONH-MBR blood flow when clinical examination data were included in the analyses.…”
Section: Discussionsupporting
confidence: 90%
“…It was recently reported that the sex-related differences were present in ocular blood flow in the ONH 25 , 26 . Our result showed sex-related differences of the ONH-MBR which was faster in the female group than that in the male group which agrees with earlier studies 25 , 26 . In the brain, males have lower cerebral blood flow velocity than females up to the age of 80 years 27 .…”
Section: Discussionmentioning
confidence: 95%
“…We previously found that 8-hydroxy-2′-deoxyguanosine levels were correlated with ocular blood flow 8 . We also found that ocular blood flow, especially in the vessel area of the optic nerve head, was higher in female than male subjects 21 . Finally, a significantly higher proportion of patients with advanced glaucoma are men 22 .…”
Section: Discussionsupporting
confidence: 57%
“…Consequently, several clinical studies that examined betweensubject comparisons of MBR in human ONH have been published. [23][24][25] However, LSFG measurements are affected by laser speckle signal bias due to the influence of various factors including retinal pigment epithelial scattering, laser beam reflectance, thickness of the vascular wall, and target tissue absorption. Therefore, interpretation of MBR comparison between different subjects, different eyes, or even different retinal locations must be done with caution.…”
Section: Discussionmentioning
confidence: 99%